2017
DOI: 10.1111/1462-2920.13605
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteomics and metabolomics suggests symbiotic metabolism and multimodal regulation in a fungal‐endobacterial system

Abstract: Many plant-associated fungi host endosymbiotic endobacteria with reduced genomes. While endobacteria play important roles in these tri-partite plant-fungal-endobacterial systems, the active physiology of fungal endobacteria has not been characterized extensively by systems biology approaches. Here, we use integrated proteomics and metabolomics to characterize the relationship between the endobacterium Mycoavidus sp. and the root-associated fungus Mortierella elongata. In nitrogen-poor media, M. elongata had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…For instance, the closely related endosymbiont B. rhizoxinica provides its host R. microsporus bacterially derived toxins that facilitate plant tissue invasion by the fungal host offsetting the physiological cost of hosting endobacteria (Lackner et al ., ). Proteomics analysis of the same cured and uncured isolates of Mortierella (AG77) presented here show that the metabolism of the fungal host and bacterium are independent but closely intertwined (Li et al ., ). Although the types of trade‐offs involved in the Mortierella‐Mycoavidus symbiosis are not fully clear yet, the presence of secondary metabolite gene clusters within the M. cysteinexigens (AG77) genome offers intriguing potential tradeoff.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the closely related endosymbiont B. rhizoxinica provides its host R. microsporus bacterially derived toxins that facilitate plant tissue invasion by the fungal host offsetting the physiological cost of hosting endobacteria (Lackner et al ., ). Proteomics analysis of the same cured and uncured isolates of Mortierella (AG77) presented here show that the metabolism of the fungal host and bacterium are independent but closely intertwined (Li et al ., ). Although the types of trade‐offs involved in the Mortierella‐Mycoavidus symbiosis are not fully clear yet, the presence of secondary metabolite gene clusters within the M. cysteinexigens (AG77) genome offers intriguing potential tradeoff.…”
Section: Discussionmentioning
confidence: 97%
“…The benefits that the endobacteria provide to the fungal partner remain largely unknown, although recent studies on other fungal-bacterial interactions have given some hints Li et al 2017). In a previous study, we combined next-generation sequencing, molecular biology, and cell physiology analyses to compare G. margarita containing CaGg (B+ line) with a "cured" line of the fungus that lacks CaGg (B-line) obtained under laboratory conditions (Lumini et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In one case only it has been demonstrated that they are a biologically active component of the symbiosis: a Glomus ( Rhizophagus ) strain free of the GRF1V‐M virus (a virus related to the Giardia‐like virus described in this work) produced a higher amount of spores and promoted plant growth more efficiently than the fungal line containing the virus (Ikeda et al ., ). Similarly a fungal strain of Mortierella elongata cured from its endobacteria produces higher spore numbers and grows better (Li et al ., ). Nevertheless, virus and endobacterial association with AMF seem to be fairly common in nature, raising the possibility of some ecological advantage difficult to measure in the laboratory experimental conditions, where most of the intra‐ and interspecies competition aspects are not under scrutiny.…”
Section: Discussionmentioning
confidence: 97%